The Cellular and Molecular Basis of Bitter Tastant-Induced Bronchodilation - Zhang, Cheng-Hai (Public Library of Science, 2013)
Bronchodilators are a standard medicine for treating airway obstructive diseases, and β2 adrenergic receptor agonists have been the most commonly used bronchodilators since their discovery. Strikingly, activation of G-protein-coupled bitter taste receptors (TAS2Rs) in airway smooth muscle (ASM) causes a stronger bronchodilation in vitro and in vivo than β2 agonists, implying that new and better bronchodilators could be developed. A critical step towards realizing this potential is to understand the mechanisms underlying this bronchodilation, which remain ill-defined. An influential hypothesis argues that bitter tastants generate localized Ca(2+) signals, as revealed in cultured ASM cells, to activate large-conductance Ca(2+)-activated K(+) channels, which in turn hyperpolarize the membrane, leading to relaxation. Here we report that in mouse primary ASM cells bitter tastants neither evoke localized Ca(2+) events nor alter spontaneous local Ca(2+) transients. Interestingly, they increase global intracellular [Ca(2+)](i), although to a much lower level than bronchoconstrictors. We show that these Ca(2+) changes in cells at rest are mediated via activation of the canonical bitter taste signaling cascade (i.e., TAS2R-gustducin-phospholipase Cβ [PLCβ]- inositol 1,4,5-triphosphate receptor [IP3R]), and are not sufficient to impact airway contractility. But activation of TAS2Rs fully reverses the increase in [Ca(2+)](i) induced by bronchoconstrictors, and this lowering of the [Ca(2+)](i) is necessary for bitter tastant-induced ASM cell relaxation. We further show that bitter tastants inhibit L-type voltage-dependent Ca(2+) channels (VDCCs), resulting in reversal in [Ca(2+)](i), and this inhibition can be prevented by pertussis toxin and G-protein βγ subunit inhibitors, but not by the blockers of PLCβ and IP3R. Together, we suggest that TAS2R stimulation activates two opposing Ca(2+) signaling pathways via Gβγ to increase [Ca(2+)](i) at rest while blocking activated L-type VDCCs to induce bronchodilation of contracted ASM. We propose that the large decrease in [Ca(2+)](i) caused by effective tastant bronchodilators provides an efficient cell-based screening method for identifying potent dilators from among the many thousands of available bitter tastants.